NILAI-NILAI YANG TERKANDUNG DALAM LIRIK LAGU PENGIRING TARIAN "TEBE" KARYA VESTER NAHAK (TEORI DEKONSTRUKSI JACQUES DERRIDA) - Manek, Veronika Matilde; Djuli, Labu; Djokaho, Margareta P.E. (Jurnal Lazuardi, 2024)
This research is entitled "Values Contained in the Lyrics of the Song Accompanying the Dance "Tebe" by Vester Nahak (Jacques Derrida's Deconstruction Theory). The problem in this research is what values are contained in the lyrics of the song accompanying the dance "Tebe" by Vester Nahak and what factors influence the emergence of these values. This study aims to analyze the values contained in the lyrics of the song accompanying the dance "Tebe" by Vester Nahak and the factors that influence the emergence of these values. The research method used in this study is a qualitative descriptive method, namely the data obtained in the form of words, not numbers, where researchers conduct observations, conduct interviews with informants, documentation, and make conclusions. The theory used in this study is Jacques Derrida's Deconstruction theory. The results of this study indicate that there are values contained in the lyrics of the accompanying dance song "Tebe" by Vester Nahak, namely social values and cultural values which are divided into several other forms of values such as social values which are divided into 2 parts, namely 1) Material Values and 2) Spiritual Values and cultural values which are divided into 4 parts, namely 1) Human Relations with Nature, 2) Human Relations with Society, 3) Human Relations with Others, 4) Human Relations with Themselves, and there are 2 factors that influence the emergence of these values, namely 1) Environmental and Cultural Factors and 2) Audience Factors.